Between a rock and a hard place: Negotiating Dependencies and Precarity in the On-Demand Economy - Hulikal Muralidhar, Srihari; Bossen, Claus; O'Neill, Jacki (Journal of Computer-Supported Cooperative Work, 2022)
On the one hand, there is growing evidence of ride-hailing platforms’ adverse impact on drivers. On the other, hundreds of thousands of drivers continue to work on these platforms. Why? What are the exit barriers or costs that they face? What considerations propel their continued usage over time? By drawing upon a qualitative study with 13 auto-rickshaw drivers using Ola, a ride-hailing platform similar to Uber in India, we show that drivers continue to use ride-hailing platforms despite little benefit. The paper illustrates how the platform nudges drivers and customers in opposite directions, resulting in adversarial interactions between the two. The duopolistic nature of the urban taxi market in the country, paralleled by a shift of more and more customers from street-hailing to app-based hailing over time, has forged new dependencies for drivers on these platforms for their livelihoods. Such dependencies, coupled with opaque, questionable practices by the platforms, have destabilized their work and financial lives. The paper examines the key aspects that have heightened the precarity that drivers experience and disempowered them in relation to both the platform-business and customers. Our findings also reveal some ancillary benefits for drivers from their use of ride-hailing applications as first-time internet/smartphone users. The paper concludes with some platform and market design implications that can improve customer-driver interaction as well as make the marketplace fairer and more equitable and protect drivers’ welfare.